A security framework for mHealth apps on Android platform - Hussain M.; Al-Haiqi A.; Zaidan A.A.; Zaidan B.B.; Kiah M.; Iqbal S.; Iqbal S.; Abdulnabi M. (Elsevier Ltd, 2023)
Android (operating system); Data privacy; Energy utilization; Health risks; mHealth; Android platforms; Android securities; Effectiveness and efficiencies; Experimental evaluation; Mobile applications development; Mobile Health (M-Health); Mobile operating systems; Security; Mobile security